Effects of Children's Trait Emotional Intelligence on Digital Game-Based Learning. Issue 4 (16th March 2019) - Yang, Jie Chi; Quadir, Benazir; Chen, Nian-Shing
ABSTRACT: Previous studies have shown that trait emotional intelligence (EI) is an important factor affecting children's learning performance in physical instruction settings. However, there have been very few studies exploring the effects of children's high- or low-trait EI levels on both gaming performance and learning performance in digital game-based learning environments. Therefore, in this study, we developed a game-based English learning environment to investigate how different levels of trait EI would affect children's gaming performance and learning performance. A total of 51 third-grade elementary school students participated in this study. The students' trait EI was measured by a modified version of the Trait EI Questionnaire-Child Form. The students' gaming performance was evaluated by the achievement of badges, and their learning performance was assessed by a paper-based examination after playing the game. The collected data were analyzed using Pearson correlation analysis and independent samples t tests. The results showed that there were significant correlations between trait EI, gaming performance, and learning performance; this implies that trait EI had a significant relationship with both gaming performance and learning performance. Moreover, the results showed that there was a significant correlation between the gaming performance and learning performance for those students with low-trait EI. However, the results showed that gaming performance and learning performance were not significantly correlated for the high-trait EI students. A subsequent analysis showed that the high-trait EI students' gaming performance and learning performance were significantly better than those with low-trait EI.